Quantifying the unique mechanical properties of irreversibly sickled cells in sickle cell disease - Dillon C. Williams; John M. Higgins; David K. Wood (Blood Vessels, Thrombosis & Hemostasis)
Abstract: We developed a platform to measure the oxygen-dependent mechanical properties and oxygen saturation of individual irreversibly sickled cells (ISCs). We identified and measured ISCs from a cohort of 10 individuals with sickle cell disease. ISCs were found to have an average shear surface modulus 20 times that of nonsickled cells and a sixth that of red blood cells (RBCs) with detectable hemoglobin polymer. We found that the number of ISCs was significantly reduced at 53 mm Hg oxygen compared with ≥91 mm Hg oxygen, suggesting that these RBCs can still form polymer under hypoxia. We also found that the fraction of ISCs present in a blood sample had a negative correlation with donor fetal hemoglobin (HbF) fraction, suggesting that HbF could play a role in mitigating occurrence of ISCs.